Predictive value of hematologic indices in COVID-19 disease outcomes - Fatemeh Nejatifar; Ali Alavi Foumani; Saman Maroufizadeh; Bardia Afsharian; Zahra Chegini; Amir Mohammad Ghanbari (Journal of Current Oncology and Medical Sciences)
Introduction: COVID-19 was declared a worldwide concern for public health in January 2020 by the World Health Organization. Most patients manifest mild symptoms. In more severe cases it can lead to sepsis, acute respiratory distress syndrome and other organ dysfunction. Lymphopenia, increased inflammatory markers and dysregulated liver enzymes are observed in many patients and is related to higher mortality rates. Materials and Methods: We evaluated two hundred and sixty-eight patients in this study. All patients had dyspnea, and O2 saturation below 93% and were tested positive for COVID-19 through RT-PCR. Patients’ demographic, clinical and paraclinical information were obtained on admission and disease outcomes were assessed based on these data. The evaluated indices were previously shown to be altered in patients with different disease outcomes. Results: From a total of 268 included patients, 40% had severe disease, 29% were admitted to ICU, 22% required mechanical ventilation and 24% died during hospitalization. WBC counts, neutrophil counts, NLR, serum LDH activity and serum albumin levels were the most powerful factors in predicting disease outcomes. Conclusion: COVID-19 disease severity and outcomes were affected by hematologic indices and laboratory results.